A gestão da informação e do conhecimento como subsídios para a geração de inovação - Silva, Elaine da [UNESP] (2013)
Innovation is presented as a crucial element for the survival and development of organizational environments in the current Information and Knowledge Society. For companies, innovation is the possibility to become more competitive and, for nations it represents advances in social and economic spheres. Therefore, policies and strategies that promote innovation arise both nationally and in isolation in an organization. Likewise, the formulation of indicators for measuring innovative activity in countries or productive sectors has become common. With the proposal to leverage the innovation generation, countries have structured the National Innovation Systems (NIS). These systems argue that innovation is the result of joint actions of several agents, among which stand out companies, universities, laboratories, research centers and development agencies in the public and private sectors. Assuming that knowledge is the most important resource for the generation of innovation and therefore to the success of NIS, it is understood that processes of Information and Knowledge Management need to integrate the actions of the components of NIS. Thus, analyzing the actions proposed for the management of projects and processes related to innovation, identifying their contemplation or not the activities of the Information Management (IM) and Knowledge Management (KM) in an organization potentially integral Brazilian NIS is the problem of this research. With the most important objective, sought to analyze options for the projects management and processes related to innovation, identifying the respective contemplation or not of activities of IM and KM at the organization.The universe chosen for the survey comprises the Serviço Nacional de Aprendizagem Industrial (SENAI) in the State of São Paulo... (Complete abstract click electronic access below)